A 2-Year Follow-Up of Oxidative Stress Levels in Patients With ST-Segment Elevation Myocardial Infarction: A Subanalysis of the ALPS-AMI Study. (March 2015) - Abe, Naoyuki; Kashima, Yuichiro; Izawa, Atsushi; Motoki, Hirohiko; Ebisawa, Souichiro; Miyashita, Yusuke; Imamura, Hiroshi; Ikeda, Uichi
We sought to determine whether serial measurements of oxidative stress levels could serve as a predictive marker for cardiovascular (CV) events in patients with ST-segment elevation myocardial infarction (STEMI). Biological antioxidant potential (BAP) levels were measured at admission and at 6, 12, and 24 months in 69 patients with STEMI. The CV events abruptly increased 6 to 10 months after successful percutaneous coronary intervention in patients with STEMI, and the 6-month BAP levels were significantly lower in patients with CV events (2456 μmol/L [interquartile range: 2237-2615 μmol/L]) than in those without (2849 μmol/L [2575-2987 μmol/L], P < .001). A decreased 6-month BAP level was an independent and significant predictor of long-term CV events (hazard ratio = 2.45; 95% confidence intervals 1.10-5.78; P = .04). Our findings suggest that serial changes in antioxidant capacity, assessed by BAP levels, may serve as a predictive marker for CV events after STEMI.